Reformasi Dan Dinamika Hukum Islam Pada Masa Pemerintahan Umar Bin Khattab - Ardian Rizky; M. Asep Rahmatullah; Ahmad Mubarok; Sanin Sudrajat; Rachmatullah Jundi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the implementation of Islamic law during the reign of Umar ibn al-Khattab, a pivotal phase in the historical development of the Islamic political system. Umar, the second caliph after the Prophet Muhammad, was known for his success in integrating the principles of Sharia into a solid and well-organized governmental structure. This research focuses on his leadership biography, legal thought, and strategic policies enacted throughout his caliphate. Using a qualitative descriptive approach through literature review, the study reveals that Umar upheld Islamic law not only through textual adherence to the Qur’an and Sunnah but also through dynamic ijtihad to address emerging social, economic, and political challenges. Notable innovations included the reform of war booty (ghanimah) land distribution, the suspension of hudud punishments during famine, the establishment of an independent judicial system, and the creation of financial and administrative institutions. Umar also formed the Majlis al-Shura (consultative council), instituted the Hijri calendar, and implemented taxation systems and social security policies. These reforms laid a foundational framework for the development of fiqh al-siyasah (Islamic political jurisprudence) and Islamic governance. The study concludes that the caliphate of Umar ibn al-Khattab marked the beginning of institutionalized Islamic law—dynamic, contextual, and firmly rooted in the principles of justice and public welfare